Genetic variability, heritability, and path analysis for agronomic characters in hybrid maize - Priyanto, Slamet Bambang; Efendi, Roy; Zainuddin, Bunyamin (Kultivasi, 2023)
Genetic parameters, which include genetic variability, heritability, and correlation between characters, are essential factors in the selection process. This study aims to: 1) determine the genetic variability and heritability for agronomic characters in hybrid maize and 2) determine the characteristics that directly affect hybrid maize yield. The experiment was conducted at Indonesian Cereal Research Institute (ICERI) Maros from June to October 2021. Fourteen maize hybrids genotypes were arranged in a randomized block design (RBD) with four replications. The observed traits were plant height, ear height, stalk diameter, leaf angle, leaf length, leaf width, days to anthesis, days to silking, days to maturity, number of harvested plants, number of harvested ears, fresh ear weight, shelling percentage, moisture content, ear length, ear diameter, number of rows per ear, number of seeds per row, 1000 seeds weight and yield. The results showed that agronomic characters with high heritability and broad genetic variability were plant height, ear height, leaf angle, leaf length, ear diameter, and 1000 seeds weight. The characters that most influence final yield were fresh ear weight and shelling percentage